The Role of Resveratrol in the Inflammatory Bowel Diseases - Lima, Tainah Aparecida; Marton, Ledyane Taynara; Marqui, Sâmylla Vaz de; Neto, Fernando Cunha; Goulart, Ricardo de Alvares; Barbalho, Sandra Maria (Pharmacognosy Reviews)
Resveratrol is a polyphenol that possesses several biological functions that are usually related to its modulating actions against inflammatory and oxidative processes. Hence, the objective of this review was to evaluate the effects of these substances in UC and CD. This review used studies published in the MEDLINE-PubMed (National Library of Medicine) following the PRISMA guidelines (Preferred Reporting Items for a Systematic Review and Meta-Analysis). The use of resveratrol in animal and human models has led to an improvement in disease activity indices, reduction of weight loss and improvement of diarrhea and rectal bleeding. It also led to serum reduction of inflammatory markers such as Interleukin (IL)-1α, IL-6, IL-8, Tumor Necrosis Factor (TNF)-α, Interferon (IFN)-γ and COX-2 and a significant decrease in OS. It promotes the reversal of dysbiosis and stimulates the expression of Tight Junction associated proteins, including Claudin-1, Occludin and ZO-1. Resveratrol is effective in the treatment of IBD by reducing the production of free radicals and increasing antioxidant enzymes. Besides, this polyphenol is capable of reducing the expression of inflammatory markers characteristic of UC and CD.
Keywords: Resveratrol; Antioxidant; Inflammatory Bowel Disease; Ulcerative Colitis; Crohn´s Disease